Profiling natural autoantibodies in relation to chronic obstructive pulmonary disease - Halala, Ramadan (2017)
Chronic obstructive pulmonary disease (COPD) is a complex condition involving chronic inflammation of the airways (chronic bronchitis) and destruction of airways parenchyma (emphysema). It is characterized by progressive airway limitation that is not fully reversible. Although the precise mechanisms of disease remains unclear, it has been thought that noxious materials, such as gases caused by smoking, may play role in the pathogenesis of the disease. However, only 15-20% of smokers developed COPD and non-smokers have also developed the disease, suggesting that other determinants may be involved the disease onset and other contributing factors may be exist. One such factor may be autoimmunity. COPD is accepted as an inflammatory disorder with evidence of circulating autoantibodies against variety of targets. Natural autoantibodies (nAAbs) are autoantibodies found in the circulation of healthy individuals without development of autoimmunity and they are considered to play a role in immune regulation and act as a protector in healthy individuals. However it has been suggested that nAAbs, under circumstances, may shift to be pathological autoantibodies.